Nutritional and quality attributes of fortified soy yogurt prepared by using probiotic food grade lactic acid bacteria - Sharma, Ranjana (Indian Journal of Dairy Science, 2016)
An effort has been made to form a nutritional rich product using probiotic cultures Pediococcus acidilactici L1and Lactobacillus plantarum L2 which were isolated from ‘Lassi’ a traditional beverage. In the present study physicochemical evaluation, sensory characteristics, and nutritional evaluation of soy yogurt blended with cow’s milk (50:50) with addition of flax seeds for increasing its nutritional properties has been studied. Soy yogurt was prepared as set I to VI by using these novel probiotic food grade strains in different combinations. Sensorial evaluation of this product, suggested that set VI containing Pediococcus acidilactici L1 and Lactobacillus plantarum L2 supplemented with sugar had maximum acceptability on 9 point hedonic scale. Microbial evaluation proved that there was no apparent loss in the total number of probiotic viable cells during storage of the product for a week time. So, this nutritionally enriched soy product can be used as an effective vehicle for delivering health beneficial effects to human being.